Ultrasound-guided HIFU for uterine fibroids of hyperintense on T2-weighted MR imaging with or without GnRH-analogue-pretreated: A propensity score matched cohort study - Jiang, Li; Yu, Jing-Wen; Yang, Mei-Jie; Zhong, Qiao; Chen, Jin-Yun (Frontiers in Surgery, 2022)
Objective: To compare the therapeutic effect of high-intensity focused ultrasound (HIFU) ablation and HIFU pretreated with gonadotropin-releasing hormone analogue (GnRH-a) in the treatment of hyperintense uterine fibroids on T2-weighted magnetic resonance imaging (T2WI) by using propensity score matching. Materials and Methods: 339 women with 368 hyperintense uterine fibroids on T2WI who underwent single-session HIFU ablation were enrolled, including 283 patients with 303 fibroids in the single-session HIFU (sHIFU) group and 56 patients with 65 fibroids in the HIFU pretreated with GnRH-a (Gn-HIFU) group. The signal intensity (SI) value and standard deviation (SD) value were measured based on T2WI, and the fibroids were further subdivided into heterogeneous hyperintense fibroids, slightly homogeneous hyperintense fibroids and markedly homogeneous hyperintense fibroids as 3 subgroups (HHF, sHHF and mHHF group respectively). Treatment time, sonication time, dose, non-perfused volume (NPV), NPV per sonication time, non-perfused volume ratio (NPVR), energy effect ratio (EEF) and adverse events were recorded. Results: Out of 339 patients, the median NPVR was 75.2% (interquartile range,31.5%). After propensity score matching, the matched cohort included 91 (64.5%) patients in the sHIFU group and 48 (34.5%) patients in the Gn-HIFU group. The NPVR of sHHF in the Gn-HIFU group had significantly smaller than that in the sHIFU group (60.2% versus 74.9%, P=0.005), and the NPVR of HHF in the Gn-HIFU group was higher than those in the sHIFU group (87.4% versus 72.9%, P=0.002). Conclusions: Compared with HIFU alone, the therapeutic efficacy of the heterogeneous hyperintense fibroids may be enhanced by GnRH-a pretreated with HIFU, however it is important to rule out the slightly homogeneous hyperintense fibroids.